(untitled) (Res Medica, 2014)
Wrenching myself away from Edinburgh in winter. I made two working visits of 2-3 weeks each to the University of Concepcion, in central Chile, at the invitation of Drs Carlos Gonzalez and Mario Munoz, the vice-deans of Science and Medicine respectively. My remit was to meet with undergraduate course organizers and comment on their plans for a new medical curriculum, in the light of my experience as the first course director of Year 1 of Edinburgh’s new curriculum, and as module organizer for Nutrition and Digestion, one of the six modules that make up the Biomedical Science component of this first year. Edinburgh’s new course, which originally had the slightly embarrassing title ‘Vision 2000’ , was implemented in October 1998, and has been extensively revised for the new semester system. In Concepcion the new medical curriculum was introduced in February of this year.